2012
DOI: 10.3382/ps.2012-02150
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of ovotransferrin and its hydrolysates

Abstract: Food protein-derived peptides are important components for nutraceuticals, with many biological functions as well as substantial nutritional benefits. The aim of this study was to investigate the antioxidant effects of ovotransferrin (OTF) derived from egg white and its hydrolysates (OH) prepared by hydrolyzing either with acid or enzymes (protamex, alkalase, trypsin, neutrase, flavorzyme, maxazyme, collupulin, protex, promod 278, and α-chymotrypsin). All OH showed approximately 3.2 to 13.5 times higher supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…A comparative examination of the antioxidant characteristics of hen's otrf (and its hydrolysed peptides) and superoxide anion scavenging activity revealed the former to be around 3.2–13.5 times greater [35]. Moreover, otrf-derived peptides displayed synergistic antioxidant impacts associated with vitamin C, epigallocatechin gallate, and caffeic acid [36].…”
Section: Characteristics Of Ovotransferrinmentioning
confidence: 99%
“…A comparative examination of the antioxidant characteristics of hen's otrf (and its hydrolysed peptides) and superoxide anion scavenging activity revealed the former to be around 3.2–13.5 times greater [35]. Moreover, otrf-derived peptides displayed synergistic antioxidant impacts associated with vitamin C, epigallocatechin gallate, and caffeic acid [36].…”
Section: Characteristics Of Ovotransferrinmentioning
confidence: 99%
“…Kim and coworkers [ 51 ] demonstrated that the antioxidant effects of hen’s ovotransferrin and of its hydrolyzed peptides is approximately 3.2–13.5 times higher than superoxide anion scavenging activity than Otrf, with the maximum activity displayed by octapeptides. Similar results were obtained for oxygen radical absorbance capacity assay and against the oxidative stress-induced DNA damage in human leukocytes [ 51 ]. In addition, Otrf-derived peptides showed synergistic antioxidant effects with Vitamin C, epigallocatechin gallate (EGCG), and caffeic acid [ 52 ].…”
Section: Antioxidant Activity Of Ovotransferrin and Its Peptidesmentioning
confidence: 99%
“…Functional peptides are not active within the sequence of the parent protein molecule and can be released by in vivo or in vitro processes [8]. The main procedure for obtaining bioactive peptides from food products is enzymatic hydrolysis of proteins orchestrated with the use of various enzymes of microbial, plant or animal origin [9], although chemical hydrolysis [10] or processing technologies such as heat or high-intensity pulsed electric field treatments can also be applied [11,12].…”
Section: Introductionmentioning
confidence: 99%